Differential Influence of Sample Sex and Neuronal Maturation on mRNA and Protein Transport in Induced Human Neurons - Ding, Baojin; Akter, Masuma; Zhang, Chun-Li (Frontiers in Molecular Neuroscience, 2020)
Nucleocytoplasmic transport (NCT) across the nuclear envelope (NE) is tightly regulated in eukaryotic cells and is critical for maintaining cellular homeostasis. Its dysregulation leads to aging and neurodegeneration. Because they maintain aging-associated hallmarks, directly reprogramed neurons from human fibroblasts are invaluable in understanding NCT. However, it is not clear whether NCT activity is influenced by neuronal maturation and sample sex (a key biological variable emphasized by the NIH policy). We examined here NCT activity at the single cell level by measuring mRNA subcellular distribution and protein transport in directly induced motor neurons (diMNs) from adult human fibroblasts. The results show that mRNA subcellular distribution but not protein transport is affected by neuronal maturation stages, whereas both transport processes are not influenced by the sample sex. This study also provides quantitative methods and optimized conditions for measuring nucleocytoplasmic transports of mRNAs or protein cargos, establishing a robust way for future functional examinations of NCT activity in directly induced neurons from diseased human patients.